Metabolism and Microstructure of the Small Intestine Wall in Patients With Colorectal Cancer - M. V. Bagryantsev; M. G. Ryabkov; E. L. Bederina; M. M. Loginova; A. V. Bazayev; A. I. Abelevich; I. L. Dezortsev; S. S. Bunova; M. V. Shirmanova; V. I. Shcheslavskiy; E. B. Kiseleva (Неотложная медицинская помощь)
RELEVANCE In patients with colorectal cancer (CRC), the normal small intestine, located outside the pathological focus, undergoes changes that may be the cause of digestive dysfunction after radical surgery to remove the tumor.The assessment of metabolic and microstructural changes in the ileum mucosa in patients with colorectal cancer is necessary to correct the algorithms of postoperative therapy and enteral nutrition. Modern means of optical bioimaging are potentially capable of solving this complex diagnostic problem.AIM OF STUDY To study the features of metabolism and morphological structure of the wall of a conditionally normal small intestine in the mucosa in patients with stage 1–3 CRC using macro- FLIM and optical coherence tomography (OCT).MATERIAL AND METHODS The object of the study was the wall of the ileum (66 samples) from the mucosal side of patients with histologically confirmed CRC stages 1–3 with tumor location in the right sections of the colon. Eight samples were obtained from patients with stage 1 CRC, 38 samples were obtained from patients with stage 2 and 20 samples were obtained from patients with stage 3 tumor. The volume of surgical intervention is right-sided hemicolectomy with total mesocolonectomy, CME (D2 lymph node dissection). Fresh tissue samples were examined using fluorescent lifetime macroimaging (macro-FLIM ) and OCT, followed by histological analysis of the material.RESULTS According to a histological study in the small intestine of patients with stage 1 CRC, the mucosa is covered with a normal single-layer prismatic border epithelium. In the intestine samples of patients with stage 2 CRC, mucus hypersecretion with areas of fibrosis and vascular congestion was observed. At the 3rd stage of CRC, the mucous membrane of the small intestine was loose, with local thickenings, areas of fibrosis with severe leukostasis, and foci of atrophy. None of the samples showed histological signs of a malignant tumor.According to OCT data, in the mucous membrane of the small intestine in patients with the 1st and 2nd stages of CRC, the contours of the villi and, partially, the crypts were well visualized. The structure of the villi was smooth, not coarse, and the shape was regular. In patients with stage 3 CRC, the contours of the crypts and villi were indistinct. There were no differences in the OCT picture between histologic preparations in the 1st and 2nd stages of CRC: the structure of the villi of the small intestine was clear, the shape was unchanged. According to FLIM data, statistically significant differences were revealed in the mean fluorescence lifetime values of reduced nicotinamide dinucleotide (phosphate) NAD(P)H (τm) between 2nd and 3rd (p=0.031), 1st and 3rd (p=0.018) by CRC stages. At the 1st stage of CRC τm was 1.61 [1.30; 2.02] ns, at the 2nd stage 1.50 [1.36; 1.73] ns, at the 3rd stage 1.37 [1.22; 1.51] ns. The FLIM results suggest an increase in the role of glycolysis in enterocyte energy metabolism along with progression of the CRC stage.CONCLUSION In patients with cancer of the right colon, lesions of the microstructure of the mucous membrane were revealed in the ileum not affected by the malignancy. At the same time, the severity of microstructural disorders in the wall of the small intestine is associated with the stage of tumor development in the colon. Bioimaging technologies, namely, methods of optical coherence tomography and fluorescence lifetime macroimaging, made it possible to objectively display microstructural and metabolic disorders in the ileum wall. The data of optical colorectal tomography demonstrated differences in the structural picture of the intestinal villi in patients with stages 1–2 and 3 of colorectal cancer. Results of fluorescence lifetime macroimaging of the metabolic cofactor nicotinamide dinucleotide (phosphate) confirmed an increase in the role of glycolysis in the energy metabolism of enterocytes along with an increase in the stage of colorectal cancer. The identified disorders in the state of the small intestine develop in patients with colorectal cancer before surgery and are highly likely to be an important pathogenetic link of malabsorption in the postoperative period. If the hypothesis is confirmed, the developed algorithm for the complex diagnosis of microstructural and metabolic disorders in tissues will expand the possibilities for the rehabilitation of patients with cancer of the right colon.